Preparation and Evaluation of Sustained Release Venlafaxine HCl Microspheres (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The aim of this study was to formulate and evaluate sustained release microsphere of Venlafaxine HCl (VF-HCl). It has many side effects with a half life around 5 hr. To reduce the adverse actions due to burst effect a sustained release (SR) Eudragit RS-100 microspheres embedded VF-HCl was formulated. The VF-HCl microspheres were prepared by oil in oil (O/O) solvent evaporation method. Drug and Polymer interaction for formulated SR Eudragit RS-100 microsphere embedded on VF-HCl was characterized by FT-IR and X-RD studie. The result showed that there is no interaction between the drug and polymer. Surface morphology of formulation carried out by FE-SEM showed good spherical geometry and uniformity in size and shape. It can be concluded that the formulated VF-HCl microspheres using widely accepted O/O method and polymer were capable for exhibiting sustained release formulation with decreasing dosing frequency thereby minimizing the occurrence of side effects with improved bioavailability. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21867 Dhaka Univ. J. Pharm. Sci. 13(1): 83-91, 2014 (June)